2007
DOI: 10.1021/cm071457b
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Bioprocesses with Inorganic Surfaces:  Layered Clay Hemostatic Agents

Abstract: Layered clays are shown to have a wide range of blood-clotting properties that appear to be influenced by surface charge. The most active clay clotting agent is as effective as a commercial zeolite hemostatic material, but does not release heat, making it a promising alternative to the zeolite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 24 publications
7
103
0
1
Order By: Relevance
“…This has been confirmed using TEG, a method that has been used to characterize various aluminosilicate materials for hemostasis [18]. It should be noted that the observed hemostatic effects of all agents, could not be attributed to an increase in blood viscosity, because in a control study where no calcium was added, no coagulation effects (i.e., no changes in blood viscosity) were observed in terms of R, α and MA values.…”
Section: Discussionsupporting
confidence: 53%
“…This has been confirmed using TEG, a method that has been used to characterize various aluminosilicate materials for hemostasis [18]. It should be noted that the observed hemostatic effects of all agents, could not be attributed to an increase in blood viscosity, because in a control study where no calcium was added, no coagulation effects (i.e., no changes in blood viscosity) were observed in terms of R, α and MA values.…”
Section: Discussionsupporting
confidence: 53%
“…However, it has been suggested that the modification introduced in the Mt changes substantially its behavior in the experimental model (Maisanaba et al, 2014a). Baker et al (2007) reported that the changes in clay structure and surface property may alter their response to blood-clotting. Therefore, it seems that the organo-modifiers used are the responsible for the higher toxic effects observed in the endothelial cells.…”
Section: Tablementioning
confidence: 99%
“…Desenvolvimentos recentes sobre as argilas têm ampliado sua aplicação além das convencionais como nanocompósitos, adsorventes e catalisadores. Novas aplicações para argilas têm avançado para muitas aplicações biomédicas incluindo sistemas de liberação controlada de drogas, agentes hemostáticos e agente antibacteriano, sendo concluído que a MMT pode ser considerada segura para uma infinidade de aplicações [3][4][5][6][7] . [10] .…”
Section: Introductionunclassified